PELAKSANAAN PEMBINAAN KEPRIBADIAN BAGI WARGA BINAAN PADA MASA PANDEMI COVID-19 DI LAPAS KELAS IIA JAMBI - Vyolicha, Pani; Muhammad, Ali; Tando, Cahyoko Edi (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The emergence of the Covid-19 virus has made several countries in the world implement a change in behavior or habits to continue carrying out activities as usual but by always implementing health protocols in the midst of the Covid-19 pandemic or better known as New Normal. In addi-tion, the emergence of the Covid-19 virus has made all institutions or agencies experience enormous changes, especially in Indonesia. An example is the Correctional Institution, which must implement health protocols for the welfare of every individual in the Correctional Institution, both employees and prisoners. With the implementation of the health protocol in Correctional Institutions, this makes the implementers of self-reliance development in Correctional Institutions obliged to prioritize security and comfort for prisoners when conducting coaching. The inde-pendence development program at the Jambi Correctional Institution aims to make every inmate an expert in a field, and when the sentence has expired, prisoners are able to implement it in an environment outside the Correctional Institution. This study uses a qualitative method, and the purpose of this study is to measure the fulfillment of the rights of prisoners in the independence development program in the new normal era, also know the strategies applied in the midst of correctional problems in the fulfillment of human rights. So the conclusion is that the Peniten-tiary makes a policy, and every individual in the Correctional Institution must comply with the health protocol that has been established.